Damage-free highly efficient polishing of single-crystal diamond wafer by plasma-assisted polishing. Issue 1 (2018) - Yamamura, K.; Emori, K.; Sun, R.; Ohkubo, Y.; Endo, K.; Yamada, H.; Chayahara, A.; Mokuno, Y.
Abstract: Single-crystal diamond (SCD) is considered to be an ideal material for next-generation power devices. Plasma-assisted polishing (PAP) without using an abrasive was applied to polish SCD fabricated by chemical vapor deposition. Argon-based plasma containing water vapour was used in the PAP to modify the surface of polishing plate and SCD (100), and SCD was polished under a polishing pressure ranging from 10 to 52.6 kPa. Raman spectroscopy measurement showed that there was no residual stress on the polished SCD surface, and a polishing rate of 2.1 μm/h and a surface roughness of 0.13 nm Sq were obtained.